Decoding policy mobility through a rhizomatic lens: spatiotemporal folding and power topology in translocal governance - Jie Guo; Hong‘ou Zhang (Humanities & Social Sciences Communications)
Abstract This paper proposes an analytical framework to deconstruct the complexity of policy governance in globalization. Challenging traditional models’ static assumptions and linear diffusion narratives, it advances a dynamic perspective rooted in Deleuze’s rhizomatic theory and topological principles, conceptualizing policy formation as contingent intersections and topological emergence among cross-local knowledge nodes. Three analytical innovations transcend “global-local” binaries: (1) Rhizomatic evolution replaces linear transfer, emphasizing nonlinear knowledge connectivity and epistemic mutations across nodes; (2) Spatiotemporal folding reveals policy innovation emerge in the overlap of “near and far” policy references and historical sedimentation and future projections; (3) Topological power analysis uncovers entangled explicit/implicit power structures in global policy governance networks. By tracing policies’ processual emergence and the spatiotemporal dynamics behind it, the study clarifies the “geography of power relations” behind global knowledge production while offering a tool for navigating “global flows”—“local practices” dialectics. This broadens the analytical scope of policy mobility research and offers a alternative perspective for tackling policy governance challenges.